2020
DOI: 10.52006/main.v2i2.89
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Public Libraries in Negros Occidental, Philippines

Abstract: This descriptive research examined the state of public libraries in Negros Occidental as to its compliance with RA 7743; its performance based on standard requirement; and implementation of greening practices to 31 administrators and 379 users. Findings revealed that most of the provisions of the law were not complied as indicated by the number of municipalities without libraries, the appointment of a non-professional librarian, and the inadequacy of budget allocation.  Likewise, assessors find their performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
4
4
0
Order By: Relevance
“…The results suggest that most municipal libraries in Iloilo Province did not conform to the stipulations of the Standards regarding the provision of sufficient equipment for a conducive learning environment. Moreover, the study supports the findings of the previous studies about the unavailability of Internet connectivity for public use in most public libraries (Alaya-ay, 2013; Laspinas, 2014; Macapagal, 2018; Tuble and Bayoneta, 2019). This is a sad reality despite the increasing importance of the Internet in supporting a range of services such as e-government, jobs and employment, health information, and education (Bertot et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results suggest that most municipal libraries in Iloilo Province did not conform to the stipulations of the Standards regarding the provision of sufficient equipment for a conducive learning environment. Moreover, the study supports the findings of the previous studies about the unavailability of Internet connectivity for public use in most public libraries (Alaya-ay, 2013; Laspinas, 2014; Macapagal, 2018; Tuble and Bayoneta, 2019). This is a sad reality despite the increasing importance of the Internet in supporting a range of services such as e-government, jobs and employment, health information, and education (Bertot et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Some do not even have a budget. The findings confirm some local studies’ findings stating that the Philippines’ municipal libraries were operating with an insufficient budget, while some did not have a budget at all (Alaya-ay, 2013; Laspinas, 2014; Tuble and Bayoneta, 2019). The findings of the studies mentioned above were confirmed by Macapagal (2018), stating that some public libraries in the country were operating with at most Php1000.00 annual budget.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations